TRANSCENDENTAL URGENCY OF LITERATURE - Taufiqurrohman Taufiqurrohman (Tarbawi : Jurnal Pendidikan Islam, 2014)
ABSTRACTThis study is aimed at socializing the importance of using literature. Due to the fact that Indonesian people hold tightly on religion, so this study uses the explanation of literature in transcendental things. The explanation here uses two samples as the topics of transcendental things. Those are literature in Al-Qur'an and in Sufi poems. Result of study on Al-Qur'an shows that God uses literature method. Poem is in every part of Surahs. Prose also exists in many parts of it. Result of study on Sufi poems shows that Sufis love to express their spiritual experiences through poetry. It is proved by the existence of so many Sufi poets in the world throughout history have written poems to express their personal experiences. It is also the fact that they write poems as their medium to get closer to their God. The conclusion can be drawn here is that both Al-Qur'an and religious magnate use method of literature in conveying the teaching. That's why it is urgent for our society to more advance literature.Keywords: Transcendental, Literature, Al-Qur'an, Sufi Poetry.ABSTRAKKajian ini bertujuan untuk mensosialisasikan pentingnya penggunaan sastra. Berkaitan dengan fakta bahwa orang-orang Indonesia yang menempatkan agama sebagai sesuatu yang paling penting dalam kehidupan mereka, maka kajian ini menggunakan pendekatan transendental dalam menjelaskan pentingnya sastra. Penjelasan dalam kajian ini menggunakan dua sampel topik transendental. Dua topik tersebut adalah sastra dalam AJ-Qur'an dan dalam puisi-puisi Sufi. Hasil kajian akan topik Al-Qur'an menunjukkan bahwa Tuhan menggunakan po/a sastra dalam menurunkan wahyu. Puisi terdapat di semua surat dalam Al-Qur'an. Prosa juga ada di banyak bagian surat. Hasil kajian terhadap puisi Sufi menunjukkan bahwa para Sufi suka mengekspresikan pengalaman spiritual mereka melalui puisi. Hal ini bisa dibuktikan dari112 I Jurnal Tarbawl Vol. II. No. 2. Jull - Desember 2014adanya banyak tulisan puisi Sufi yang terbentang sepanjang sejarah. Kesimpulan yang bisa diambil adalah bahwa Tuhan /ebih memilih sastra untuk menurunkan Al-Qur'an. Selain itu, para tokoh Sufi juga menggunakan po/a puisi dalam berbagi pengalaman spiritual. Dua ha/ tersebut menunjukkan betapa pentingnya penggunaan sastra bagi manusia dalam kehidupannya.Kata-kata Kunci: Transendental, Literatur, Al-Qur'an, Puisi Sufi.